Infraestrutura e comércio internacional: uma abordagem a partir do modelo gravitacional para os países da América Latina - Cruz Junior, Luiz Valdemir Ribas da (Universidade do Vale do Rio dos Sinos, 2017)
Infrastructure is a crucial point within the studies of international trade. Its provision explains not only the costs of commerce, but also its effects upon the growth and economic development. Besides this, when combined with geographical conditions, such as distance, it provides a very solid capacity of explanation about the bilateral commercial fluxes. In this sense, the goal of this work is to estimate the influence of the infrastructure on the countries of Latin America. For such, the methodology that has been used is the gravitational model in panel-data for the period between 2006 and 2013. The sample of countries were divided in two groups. The first one, considered the commerce among the countries of Latin America, composed by 15 of them. The second group was composed by the main commercial partners of the analyzed countries, a total amount of 74 countries. In the expanded sample, the results showed that the general infrastructure and the importer/exporter’s port were the factors that most affect the commerce. The countries of the region were quite sensible to the infrastructure of the exporter, given that the general infrastructure of the exporter countries had generated negative effects in the commerce of Latin America. Regarding only to the trade between countries of Latin America, the roads showed harmful results for the commerce. Thus, it was possible to verify potentialities for the expansion of the commerce, as of improving the infrastructure’s roads quality - so important in the internal cohesion of those countries. It was also verified that the region has a gap on the efficient provision of infrastructure, spoiling its countries in terms of obtaining bigger profits from the commerce.
Keywords: Infraestrutura; Geografia; América Latina; Modelo gravitacional; Infrastructure; Geography; Latin America; Gravity model; ACCNPQ::Ciências Sociais Aplicadas::Economia